Fostering Values-Driven Sustainability Through an Ex-Post Capacities Lens - Jindra Cekan/ova (The Evaluation Center at Western Michigan University, 2023)
Monitoring and evaluation (M&E) work is driven by an array of values held by funders, implementers, M&E experts, and the project participants themselves. Some are explicit, such as embedding equity or democratization values into aid projects. Some are assumed, such as the truth of "values-neutral" evaluation or that long-term sustainability will result from projects. The author espouses Quinn Patton's "activist interventionist change-committed evaluation" in pushing for ex-post evaluation of much development aid programming's untested hypothesis about the sustainability of results without proof post-project. Programming approaches can make development results more sustained and can be monitored and evaluated. One set of activities is the participatory involvement of national and local stakeholders from the onset and during all stages of programming. The activism includes M&E experts pushing to include listening to local participants and partners via mixed-methods evaluations, especially by hiring local evaluators, and asking not only about donor-expected results but also about locally emerging outcomes, along with sharing learning at all levels, from local to donors. Focusing on the sustainability of outcomes and impacts involves those doing M&E and those involved in explicit sustainability planning from design, with national project stakeholders at every step. This chapter focuses on a roadmap of capacities and tools needed to foster sustainability pre-exit drawn from a decade of ex-post project closure evaluations. Current evaluators can help improve development practice and the durability of results by honing their capacities to evaluate the natural system on which most projects rest and how to foster resilience to climate change via M&E. Once this is built, transformations toward locally-driven development become possible.